Discovery of potent STAT3 inhibitors using structure-based virtual screening, molecular dynamic simulation, and biological evaluation - Liu, Weifeng; Chu, Zhijie; Yang, Cheng; Yang, Tianbao; Yang, Yanhui; Wu, Haigang; Sun, Junjun (Frontiers in Oncology, 2023)
Signal transducer and activator of transcription 3 (STAT3) is ubiquitously hyperactivated in numerous cancers, making it an appealing target for therapeutic interventions. In this study, using structure-based virtual screening complemented by molecular dynamics simulations, we identified ten potential STAT3 inhibitors. The simulations indicated that compounds 8, 9, and 10 formed distinct hydrogen bonds with the Src Homology 2 (SH2) domain of STAT3. In vitro cytotoxicity assays highlighted compound 4 as a potent inhibitor of gastric cancer cell proliferation in MGC803, KATO III, and NCI-N87 cell lines. Furthermore, cellular assays confirmed the ability of compound 4 to attenuate IL-6-mediated STAT3 phosphorylation at Tyr475. Additionally, the oxygen consumption rate assays corroborated the deleterious effects of compound 4 on mitochondrial function. Collectively, our findings suggest that compound 4 is a promising lead candidate for the development of anti-gastric cancer therapeutics.